2016
DOI: 10.1016/j.seppur.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different biofilm carriers on the operation and membrane fouling of submerged membrane bioreactors

Abstract: a b s t r a c tIt has been reported that the combination process of biofilm and submerged membrane bioreactors (MBRs) can mitigate membrane fouling. In this study, the influence of using three different biofilm carriers (fixed rope carrier, moving granular carrier and moving sponge carrier) on the operation and membrane fouling of MBRs was investigated. Using rope or sponge carriers with MBR processes improved the removal efficiency of nitrogen via the creation of an anoxic part inside the carriers. However, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Furthermore, a significant R PB increase was achieved in Phase II, up to 13%. Such a result suggested that the C/N variation in Phase II determined the variation of the activated sludge features (e.g, increased production of SMPc) which have likely promoted an increase of membrane fouling due to pore blocking (Kurita et al, 2016).…”
Section: Influence Of Operational Conditionsmentioning
confidence: 99%
“…Furthermore, a significant R PB increase was achieved in Phase II, up to 13%. Such a result suggested that the C/N variation in Phase II determined the variation of the activated sludge features (e.g, increased production of SMPc) which have likely promoted an increase of membrane fouling due to pore blocking (Kurita et al, 2016).…”
Section: Influence Of Operational Conditionsmentioning
confidence: 99%
“…To address membrane fouling, moving bed biocarriers may be added directly into the activated sludge of a conventional MBR, a configuration commonly referred to as a hybrid membrane bioreactor (HMBR). The biocarriers provide mechanical scouring of the membrane surface, which reduces the thickness of the cake layer and helps to restore permeability during operation (Deng et al, 2014;Kurita et al, 2016;Nguyen et al, 2016). The influence of the biocarriers on the characteristics of the sludge has also been shown to reduce fouling, in some instances, by up to 40% (Palmarin and Young, 2019b).…”
Section: Membrane Bioreactormentioning
confidence: 99%
“…The membrane fouling mitigation mechanism of biological carriers could be divided into two categories: on the one hand, biological carriers, especially moving carriers, exert a mechanical scouring effect on the membrane surface [23]; on the other hand, the carrier improves the characteristics of the sludge mixture through biological immobilization and stabilization [24]. In recent years, many researchers carried out research on the membrane pollution mechanism of different forms of biological carriers in MBR, which laid a foundation for the application of biological carriers to alleviate MBR membrane pollution [23,25].…”
Section: Introductionmentioning
confidence: 99%